Coplanar waveguide stub filter at 2.4 GHZ 3RD order / Aizat Murtaza Abas - Abas, Aizat Murtaza (2010)
This thesis describes the design and characterization a bandpass filter (BPF) realized using coplanar waveguide (CPW) stub structures. The demonstrated CPW-BPF is centered at 2.4 GHz and is in 3rd order form. FR4 Epoxy laminate with permittivity er=5.4 and substrate thickness of 1.6mm is used in the implementation of the filter. The filter is simulated by using CAD software and Computer Simulation Technology (CST) software and then the design is fabricated on FR4 Epoxy laminate. The Coplanar waveguide stub filter is then measured using Vector Network Analyzer which then shows good agreement with the simulation results.